Mitigating contemporary copyright issues through blockchain technology : an appropriate solution to digital copyright enforcement within the EU? - Stevens-Yager, Jacob (My University, 2019)
Since the birth of the Internet, law makers both within the EU and abroad have struggled to keep pace with the rapid evolution of technology. Technology, while a key denominator of innovation across various industries, has culminated in numerous problems pertaining to copyright infringement, particularly as it concerns the enforcement of rights within the digital space. EU regulators have, through the ​E-Commerce​, ​InfoSoc​, and ​Enforcement Directive​, as well as the recently ​Proposed Directive​ on copyright, sought to advance the enforcement rights of creators within the EU in order to effectively combat these issues and provide a secure domain for protected content creation. It is the primary objective of this paper to analyse the current issues stemming from the EU’s current approach to online copyright enforcement and, more importantly, validate the potential efficacy of the blockchain technology to resolve these issues. More specifically, this thesis aims to demonstrate how the specific features of the blockchain can be utilised to either fill or support the gaps currently emanating from EU copyright law, primarily the enforcement of digital rights, as well as the legal and non-legal considerations culminating from its adoption. The primary scope of this study is narrowed towards current and future EU legislation/directives, in addition to non-legislative initiatives and policies. The integration of the blockchain within the copyright eco-system manifests numerous legal and non-legal questions pertaining to its assimilation with EU laws, as well as its own technological limitations. Acceptance of the blockchain’s core features through its assimilation within EU laws, in addition to a broader stakeholder knowledge of the technology through stronger education initiatives, would prove beneficial to right holders as a legitimate digital copyright enforcement tool, in addition to planting the seed for further innovation. This thesis paper has achieved its primary goal of demonstrating the potential of the blockchain to resolve the issue of digital copyright enforcement within the EU.
Keywords: EU copyright law, blockchain, digital copyright enforcement, copyright infringement.